The role of insurance policy in facing banking risks (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The concept of insurance policy is one of the concepts that expresses a way to face the risks that a person is exposed to in the field of his life. It is a system that involves a prior agreement between two parties through which the risk is transferred from the second party (the insured) to the first party (the insurer) in return for paying an amount Calculated was able to cover the potential loss according to certain percentages agreed upon between the two parties, and that the main goal of any scientific analysis of the risk is to choose the most appropriate policy or method to confront it, by identifying the risks and ways to address them, and the main goal is to reduce losses and limit the possibility of their occurrence.In light of this, the researchers dealt in their research with the topic (the role of insurance policy in facing banking risks), as this research included three topics. Loans)) in addition to the importance of research, the most important of which is the identification of insurance policy and its role in facing banking risks. And then he touched on the objectives of the research, the most important of which is identifying the most important determinants and obstacles to the insurance policy in banks that may hinder its implementation, and then developing ways to analyze and implement it.This research was applied in Al-Rafidain Bank, Al-Waziriyah Branch, by testing a sample of (60) individuals, including managers and employees of a branch and its employees. The statistic that reached certain results, in the light of which the two researchers reached a number of conclusions, the most important of which was the existence of a correlation and impact between the insurance policy and banking risks, when the bank applies and follows the insurance activity in its business, where the insurance industry is a safety valve for the economic system, including banks For any bank intended to achieve the desired goals. In the end, the researchers presented a set of theoretical and practical recommendations to the bank in question, based on the results that were reached, the most important of which was that the insurance contract concluded between the insured and the insured regarding insurance for borrowers or insurance for loans is necessary to obtain loans, not The existence of legislation and laws by the authority with regard to determining the dealings of insurance companies with banks, but the agreements concluded between the two parties depend on the bank in question to develop a special section concerned with banking risks.